Strategi Promosi melalui Media Sosial dan Electronic Word of Mouth untuk Komunikasi Konsumen - Erik Syawal Alghifari; Ratih Hurriyati; Puspo Dewi Dirgantari; Rohmat Sarman (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
This study discusses issues related to purchasing decisions. The research focused on the social networking community on social media facebook with a sampling technique using non-probability sampling. The method used in this research is Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis with Smart-PLS version 3.3.5 software support. The results of the study conclude that promotional strategies through social media have a positive influence on purchasing decisions. Promotional strategies through social media have a positive influence on electronic word of mouth. Electronic word of mouth has a positive influence on purchasing decisions. Electronic word of mouth mediates the effect of promotional strategies through social media on purchasing decisions. The practical implication of this research is that companies in the organic agricultural sector, especially organic rice products, are recommended to carry out promotional strategies through social media because this strategy is one of the most effective and appropriate tools in marketing, so that electronic word-of-mouth marketing will be formed, which ultimately has an impact on purchasing decisions.